Pembelajaran Berbantuan Masalah Menggunakan Software Gnuplot - Annisa Aulia Dahlan Dalimunthe; Yahfizham (Yayasan Bayt Shufiya Nusantara, 2025)
This research aims to analyze the effect of problem-assisted learning using Gnuplot software on student learning outcomes. The method used is a quantitative descriptive approach with simple linear regression analysis techniques. The research sample consisted of 30 students who had used Gnuplot in the learning process. The instrument used was a questionnaire with a four-point Likert scale. The results of the analysis show that there is a fairly strong relationship between problem-assisted learning variables and learning outcomes, with a correlation coefficient of 0.44 and a coefficient of determination of 19%. In addition, the significance test shows that Gnuplot-assisted learning has a real influence on student learning outcomes. Thus, the use of Gnuplot as a tool in problem-based learning has proven to be effective in increasing students' understanding and academic achievement.